144k views
1 vote
Solve for t. 5 (t + 3) = -3.5

User Ilyssa
by
5.6k points

1 Answer

4 votes

We are given the following equation


5(t+3)=-3.5

Let us solve the equation for variable t

Our goal is to separate the variable t

Step 1:

Divide both sides by 5 and simplify


\begin{gathered} (5(t+3))/(5)=(-3.5)/(5) \\ (t+3)=-0.7 \end{gathered}

Step 2:

Subtract 3 from both sides and simplify


\begin{gathered} t+3-3=-0.7-3 \\ t=-3.7 \end{gathered}

Therefore, the equation has been solved for t.


t=-3.7

User Pankaj Rawat
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.